EXPLORING PURA AGUNG GIRI NATHA AS THE BALI OF CENTRAL JAVA - Puji Lestari Nata; Nina Mistriani (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
This study aims to explore and analyze the tourist attractions of Pura Agung Giri Natha which is known as the "Bali of Central Java" with a focus on the aspects of religious, architectural and potential development as a tourism destination. The research method uses a qualitative approach with data collection techniques through direct observation, in-depth interviews with temple administrators, community leaders, and tourists, and documentation studies. The results of the study indicate that Pura Agung Giri Natha has a unique architecture that combines Balinese style with Javanese nuances, religious rituals that are still maintained, and captivating natural scenery. This temple not only functions as a place of worship but also has the potential as a religious and cultural tourism destination that can enrich the tourism treasures of Central Java. This study provides a new contribution to the development of religious tourism by identifying a temple management model that can maintain sacred values while accommodating tourism activities. The conclusion of the study shows the need for a sustainable development strategy by involving stakeholders to optimize tourism potential while maintaining the sanctity and sustainability of the temple.